1991
DOI: 10.1115/1.2927879
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Rotating Serpentine Passages With Smooth Walls

Abstract: Experiments were conducted to determine the effects of buoyancy and Coriolis forces on heat transfer in turbine blade internal coolant passages. The experiments were conducted with a large-scale, multipass, smooth-wall heat transfer model with both radially inward and outward flow. An analysis of the governing flow equations showed that four parameters influence the heat transfer in rotating passages: coolant-to-wall temperature ratio, Rossby number, Reynolds number, and radius-to-passage hydraulic diameter ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(50 citation statements)
references
References 0 publications
7
43
0
Order By: Relevance
“…Thus, heat transfer is enhanced on the leading side and the average Nu ratio begins to rise with Buo. For the smooth square channel, this turning point is about 0.15[17].In the second passage with radially inward flow, the observed behavior is qualitatively similar to the first passage. The average Nu ratios on the leading surface increase slightly withBuo through the entire operating range investigated.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Thus, heat transfer is enhanced on the leading side and the average Nu ratio begins to rise with Buo. For the smooth square channel, this turning point is about 0.15[17].In the second passage with radially inward flow, the observed behavior is qualitatively similar to the first passage. The average Nu ratios on the leading surface increase slightly withBuo through the entire operating range investigated.…”
supporting
confidence: 77%
“…Wagner et al ( , 1992 [16][17][18] provide a set of data in a square multi-passage channel with smooth and 90-deg ribs. They concluded that the local heat transfer coefficients increase over 200% on the trailing surface and decrease up to 60% on the leading surface compared to non-rotating results in the first pass.…”
Section: Effect Of Rotationmentioning
confidence: 99%
“…1, the passage also rotates orthogonally [1][2][3][4][5][6]. Experimental investigations focus entirely on the effects of rotation in straight ducts have also appeared [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…So experiments with rotation have been conducted to model engine cooling environments more closely. Wagner et al [5,6] systematically conducted experimental investigations on heat transfer in a four-pass rotating smooth channel. They found that the Coriolis force had a positive effect on heat transfer of trailing wall but negative effect on leading wall in the first radial outward passage.…”
Section: Introductionmentioning
confidence: 99%